Performance analysis, conceptual mapping, and emerging trends for Gum Arabic research: a comprehensive bibliometric analysis from 1916 to 2023 - Siddig Ibrahim Abdelwahab; Manal Mohamed Elhassan Taha; Abdalbasit Adam Mariod (Food Production, Processing and Nutrition)
Abstract Gum Arabic (GA) is a natural ingredient used in food, pharmaceutical, and cosmetic industries. Numerous studies have been conducted on the physicochemical properties and applications of GA. This study aimed to map knowledge and perform a bibliometric analysis of GA research (GAR) for over a century ago. A search was carried out in the Scopus database using relevant terms and Boolean operators (Gum Arabic OR Acacia gum, OR gum sudani), and data-driven documents in English were extracted. The extracted data included citations, bibliographical and geographical information, abstracts, and keywords. The CVS and BibTex data files were analyzed using VOSviewer and Bibliometrix platforms, respectively. The annual increase in GAR is incremental, consisting of 5313 documents over 108 years and produced by 27 scientific disciplines. The three most productive countries are India, China, and the United States. The rate of international co-authorship was 22.07%, with China being the most collaborative country. Food Hydrocolloids is the most prestigious source. Phillips, G.O., is the most prolific, cited, and co-cited author. Four clusters were detected based on the co-citation analysis of the authors. The most frequent terms in the GAR were “nanoparticles,” “carbon nanotubes,” “stability,” “rats,” “microencapsulation,” and ”lipase.” “Carbon nanotubes” and “microencapsulation” are evolving subjects in GAR. 2000 and 2010 are the turning points in GAR’s thematic evolution. “Ultrasound,” “Pickering emulsion,” “sensory evaluation,” “bioactive compounds,” “cytotoxicity,” and “green synthesis” are the trending topics. Our findings reveal the most common scientific research on GAR, with the physiochemical qualities of GA as a dietary and pharmaceutical constituent being the most common. The marketing, production, tapping, and processing of GA requires further investigation. Graphical Abstract